Differentiated Learning Management To Improve Students’ English Grammar Understanding - Aulyfannisah, Masayu Safira; Lian, Bukman; Nugroho, Heri Setiyo (Yayasan Sembilan Pemuda Indonesia, 2025)
This study describes the preparation, implementation and evaluation of English learning to improve students’ understanding of English grammar at SMK Negeri 6 Palembang. This research belongs to qualitative and based on postpositivism, which consists of the planning stage, data collection, data analysis, and report preparation. The data collection techniques for this study are observation, in-depth interviews, and field documentation. The technique used in data validity is data triangulation. Data analysis is carried out interactively and continuously. The results of the study show that (1) teacher preparation in differentiated learning in the process of compiling materials that are appropriate to the needs of various students, including adjusting the level of difficulty and learning style, requires dedication and a lot of time allocation; (2) with the implementation of English learning, students look happier, students feel that their learning activities are not boring, and they are more active in asking questions; and (3) evaluation of english language learning requires support from the school because most of the initiatives come from the english teacher. So, it requires more attention from the school, both in the form of training and provision of learning facilities.